Feeling Photography - Ann, Cvetkovich; Brown, Elspeth H.; Christopher, Pinney; Dana, Seitler; David L., Eng; Diana, Taylor; Elizabeth, Abel; Elspeth H., Brown; Kimberly Juanita, Brown; Leo, Spitzer; Lily, Cho; Lisa, Cartwright; et al. (Duke University Press, 2014)
This innovative collection demonstrates the profound effects of feeling on our experiences and understanding of photography. It includes essays on the tactile nature of photos, the relation of photography to sentiment and intimacy, and the ways that affect pervades the photographic archive. Concerns associated with the affective turn-intimacy, alterity, and ephemerality, as well as queerness, modernity, and loss-run through the essays. At the same time, the contributions are informed by developments in critical race theory, postcolonial studies, and feminist theory. As the contributors bring affect theory to bear on photography, some interpret the work of contemporary artists, such as Catherine Opie, Tammy Rae Carland, Christian Boltanski, Marcelo Brodsky, Zoe Leonard, and Rea Tajiri. Others look back, whether to the work of the American Pictorialist F. Holland Day or to the discontent masked by the smiles of black families posing for cartes de visite in a Kodak marketing campaign. With more than sixty photographs, including twenty in color, this collection changes how we see, think about, and feel photography, past and present.Contributors. Elizabeth Abel, Elspeth H. Brown, Kimberly Juanita Brown, Lisa Cartwright, Lily Cho, Ann Cvetkovich, David L. Eng, Marianne Hirsch, Thy Phu, Christopher Pinney, Marlis Schweitzer, Dana Seitler, Tanya Sheehan, Shawn Michelle Smith, Leo Spitzer, Diana Taylor